Scientific animations without borders - Bello-Bravo, Julia; Pittendrigh, Robert (Technical Centre for Agricultural and Rural Cooperation, 2015)
Julia Bello-Bravo and Barry Robert Pittendrigh outline an emerging strategy to connect local and global experts to create and deploy educational content for low-literate learners in the form of animated videos.